Egyptian Blue into Carboxymetylcellulose: New Dual-Emissive Solid-State Luminescent Films - Mariana Coimbra; Francesco Fagnani; Gisele Peres; Paulo Ribeiro-Claro; Juan Carlos Otero; Daniele Marinotto; Dominique Roberto; Mariela Nolasco (Molecules)
The development and characterization of a sustainable carboxymethylcellulose (CMC)-based material hosting Egyptian blue (EB) as a luminophore with emission in both the visible and NIR regions is herein presented and discussed, demonstrating its potential to be applied in a variety of applications, such as bioimaging, sensing, and security marking. Solution casting was used to synthesize the films, with citric acid (CA) as a crosslinking agent. Fully characterization was performed using attenuated total reflection (ATR) and coherent anti-Stokes Raman scattering (CARS) spectroscopy, zeta potential, UV–Vis, and photoluminescence (PL) spectroscopy, and thermal analysis techniques, such as thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The results confirm the effective crosslinking of CMC with CA within CMC–EB–CA films with 1.5 and 3% of EB. The introduction of EB retained its usual NIR emission with λem max = ~950 nm reaching quantum yield values in the range of 11.2–12.8% while also enabling a stable dispersion within the CMC matrix, as confirmed using CARS imaging and zeta potential. Additionally, the CMC films exhibited the characteristic clustering-triggered emission (CTE) in the blue region at 430 nm with a slight increase in luminescence quantum yield (Φ) from 5.8 to 6.1% after crosslinking with citric acid.